Examining the quality of work life: empirical testing indicators in the public organisation - Zahedy, Mohammad Reza; Jafari, Seyyed Asghar; Ramezan, Majid (Goodwood Publishing, 2021)
Purpose: The present study aimed to identify employees’ quality of work life indicators in public organisations and provide necessary context to improve system accountability and employees’ needs in organisations. Research methodology: To identify quality of work life indicators, authors studied theoretical research basics entirely and by considering elites’ ideas, identified main indicators by a descriptive – survey technique. Result: Based on research findings, 15 constituents were identified as work life quality indicators. Research results indicate undesired quality of work life among employees at public organisations. Of identified constituents, Safe and healthy working conditions and organisational conflict are the most important and job satisfaction and Pay/benefits are the lowest important factors. Limitations: The results only extend the understanding of the role of quality of work life in organisational effectiveness and have implications for human resource managers that may not be applicable for other positions. Contribution: The study results help organisations identify the elements that affect the QWL and help them plan to increase organisational effectiveness by increasing employee satisfaction and motivation.